Relation of Parasites in Soil with The Existence of Parasites on Farmer's Nails - Edza Aria Wikurendra; Merry Crismiati; Globila Nurika (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2021)
Worms is an infectious disease caused by parasitic worms that can endanger health. Worms that often infect and have a very detrimental impact are soil-borne worm infections or Soil-Transmitted Helminths. Soil-Transmitted Helminths still considered insignificant because it is considered not to cause harm or cause death. This study aims to determine the relationship of parasites in the soil with the presence of parasites on the nails of farmers Sumber Urip 1 Village Wonorejo, East Java, Indonesia. The research method was used observational analytic with a cross-sectional study design which involved 18 Sumber Urip 1 farmers in Wonorejo Village. The sampling technique used was Total Sampling. The bivariate analysis uses Pearson correlation with decision making using significant <0.01. The identification of parasites using the floating method in 18 soil samples contained 12 flattering pieces of hookworm larvae and roundworm eggs. While the results of parasite identification with sedimentation method in 18 nail samples of farmers, there are 11 positive hookworm larvae samples, i.e. Ancylostoma duodenale. The correlation test result showed a relationship between parasites in the soil and nails of Sumber Urip 1 farmers in Wonorejo village (significant as P < 0.01). The use of gloves and footwear (shoes) when working on agricultural land, wash hands with soap and brush nails so that dirt is lost, and consume worm medicine can prevent worms infection.